Swarm control designs applied to a non-ideal load transportation system - Chavarette, Fábio Roberto; Guilherme, Ivan Rizzo [UNESP]; Do Nascimento Jr., Orlando Saraiva; Peruzzi, Nelson José [UNESP]; Balthazar, José Manoel [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2010)
In this paper, a load transport system in platforms is considered. It is a transport device and is modelled as an inverted pendulum built on a car driven by a DC motor. The motion equations were obtained by Lagrange's equations. The mathematical model considers the interaction between the DC motor and the dynamic system. The dynamic system was analysed and a Swarm Control Design was developed to stabilize the model of this load transport system. ©2010 IEEE.
Keywords: Control design; Dynamic Systems; Inverted pendulum; Lagrange's equation; Motion equations; Transport systems; Transportation system; DC motors; Dynamical systems; Mathematical models; Transportation; Equations of motion